Polybrominated diphenyl ethers and alternative halogenated flame retardants in mollusks from the Chinese Bohai Sea: Levels and interspecific differences. (May 2019) - Fu, Lingfang; Pei, Jie; Zhang, Yuyu; Cheng, Xiaogu; Long, Shenxing; Zeng, Lixi
Abstract: Polybrominated diphenyl ethers (PBDEs) and alternative halogenated flame retardants (AHFRs) were measured in eleven mollusk species collected from the Chinese Bohai Sea. PBDEs and AHFRs were detected in all species, and their average total concentrations were in the range of 22.5–355 and 10.0–84.3 ng/g lipid weight, respectively. Decabromodiphenyl ether (BDE-209) and decabromodiphenylethane (DBDPE) were the dominant halogenated flame retardants (HFRs), contributing 22.5% to 73.6% and 3.1% to 38.3% of the total HFRs, respectively. The levels of PBDEs and AHFRs were moderate to high from a global perspective. Interspecific differences in the accumulation of PBDEs and AHFRs were characterized by heat map and cluster analysis. Composition profile differences were also observed, with higher proportions of AHFRs in gastropods than in bivalves. These species-specific differences in concentrations and profiles in mollusks were attributed to different species traits, including feeding habit, trophic level, and metabolic potential. Highlights: PBDEs and AHFRs were determined in mollusks sampled from the Chinese Bohai Sea. The concentrations of HFRs in Bohai Sea mollusks were at moderate to high levels from a global perspective. Interspecies differences in the accumulation of AHFRs and PBDEs were studied among different mollusks. Dietary habit, metabolic capacity, and trophic level were chosen to interpret species-specific bioaccumulation of HFRs.